2012
DOI: 10.5194/esd-3-233-2012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vegetation dynamics on anthropogenic climate change

Abstract: Abstract. In this study, vegetation-climate and vegetationcarbon cycle interactions during anthropogenic climate change are assessed by using the Earth System Model of the Max Planck Institute for Meteorology (MPI ESM) that includes vegetation dynamics and an interactive carbon cycle. We assume anthropogenic CO 2 emissions according to the RCP 8.5 scenario in the time period from 1850 to 2120. For the time after 2120, we assume zero emissions to evaluate the response of the stabilising Earth System by 2300.Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…A decrease from approximately 900 to 300 ppm during the Oligocene took approximately 10 million years (Beerling and Royer, 2011), which translates into an average rate of −6 × 10 −5 ppm per year. As the current rates of CO 2 change are likely unprecedented, no proxy analogues exist to deduce vegetation responses to the ongoing atmospheric and climatic changes (Prentice et al, 1993;Foster et al, 2017). Due to the coarse temporal resolution of many paleo-records, it is, however, still challenging to calculate rates at decadal or even finer temporal resolution for a direct comparison of past, present and future rates of change (but see Zeebe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A decrease from approximately 900 to 300 ppm during the Oligocene took approximately 10 million years (Beerling and Royer, 2011), which translates into an average rate of −6 × 10 −5 ppm per year. As the current rates of CO 2 change are likely unprecedented, no proxy analogues exist to deduce vegetation responses to the ongoing atmospheric and climatic changes (Prentice et al, 1993;Foster et al, 2017). Due to the coarse temporal resolution of many paleo-records, it is, however, still challenging to calculate rates at decadal or even finer temporal resolution for a direct comparison of past, present and future rates of change (but see Zeebe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Using the TRIFFID DGVM, Huntingford et al (2013) found often-substantial differences in tropical carbon stocks between transient projections for 2100 under strong climate change and committed equilibrium stocks under climate and [CO 2 ] held constant at 2100 levels. Likewise, Port et al (2012) simulated continued global uptake of carbon by the terrestrial biosphere using Max-Planck-Institute Earth System Model (MPI-ESM) following stabilization of atmospheric radiative forcing from 2100 on. These changes in carbon storage resulted both from changes in carbon storage within existing ecosystems and from vegetation dynamics leading to a change in landcover type.…”
Section: Introductionmentioning
confidence: 99%
“…2). The boundary between tropical trees and extra-tropical trees is prescribed based on the climatic limits of tropical trees computed from off-line simulations by Heinemann et al (2009) for the Eocene climate and by Port et al (2012) for the pre-industrial climate. Tropical trees have a LAI of 7 and a roughness length of 2 m. Extra-tropical trees have a LAI of 5 and a roughness length of 1 m. To facilitate comparison between the Eocene and the pre-industrial simulations, we ignore that the climatic requirements for tropical trees differ between the Eocene and the pre-industrial case.…”
Section: Simulationsmentioning
confidence: 99%
“…All preindustrial simulations start from the equilibrium climate by Port et al (2012), whose pre-industrial simulation ran for 1000 years, with dynamic vegetation cover and an atmospheric CO 2 concentration of about 280 ppm. In the first time step, we replace the mixed pre-industrial vegetation cover with dark desert, bright desert, and forests in the dark desert world, bright desert world, and forest world simulation, respectively.…”
Section: Simulationsmentioning
confidence: 99%